2015
DOI: 10.1186/s40064-015-1540-3
|View full text |Cite
|
Sign up to set email alerts
|

The stress of studying in China: primary and secondary coping interaction effects

Abstract: Answering the call for research on coping outside of the Western world, the present study confirms previous research that indicated Asians cope with stress differently from other ethnic groups. In the present study, we explore the stress-coping-adjustment model and its role in acculturation for educational sojourners in the People’s Republic of China. Using a sample of 121 recent exchange students (Asian, n = 52; non-Asian, n = 69), we administered surveys in the Fall of 2013 and 90 days later to measure stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
0
17
0
1
Order By: Relevance
“…Increases in family conflicts and emotional distress were reported during that period (62). Similarly, academic stress is widespread in most Asian societies, particularly in Chinese cultures (63,64). From a service perspective, our findings highlight the importance of identifying these potentially modifiable risk factors and developing culturally relevant preventive interventions (e.g., providing social support to improve the family environment, mindfulness interventions to relieve academic stress) to improve the clinical and psychosocial outcomes of survivors.…”
Section: Discussionmentioning
confidence: 63%
“…Increases in family conflicts and emotional distress were reported during that period (62). Similarly, academic stress is widespread in most Asian societies, particularly in Chinese cultures (63,64). From a service perspective, our findings highlight the importance of identifying these potentially modifiable risk factors and developing culturally relevant preventive interventions (e.g., providing social support to improve the family environment, mindfulness interventions to relieve academic stress) to improve the clinical and psychosocial outcomes of survivors.…”
Section: Discussionmentioning
confidence: 63%
“…With a sample of British expats residing in Singapore, Ward and Kennedy (2001) demonstrated that low levels of positive reinterpretation, along with high levels of mental disengagement and venting, predicted increased levels of depression. Similarly, English, Zeng, and Ma’s (2015) study with international students in China suggested that secondary coping was beneficial in reducing the negative effects of acculturative stress on sociocultural adjustment for non-Asian students. These findings suggest that the lack of secondary strategies can have detrimental effects for the psychosocial well-being of Westerners residing in collectivistic, Asian contexts.…”
Section: Effectiveness Of Secondary Coping Across Cultures and Ethnicmentioning
confidence: 97%
“…These investigations were designed to explore by what means people in individualistic versus collectivistic cultures deal with everyday life challenges. The second line of research has focused on the effectiveness of secondary coping during cross-cultural transition, thus aiming to understand which coping styles provide adaptive strategies when people originating from individualistic (or collectivistic) cultures are exposed to the new norm and value system of a dominantly collectivistic (or individualistic) society (e.g., English, Zeng, & Ma, 2015;Szabo et al, 2016;Wang et al, 2012;Ward & Kennedy, 2001). Schulz and Heckhausen (1999) have argued that secondary coping strategies are best researched during significant life transitions when the opportunities for exerting control are redefined or threatened.…”
Section: Secondary Coping and The Type Of Stressormentioning
confidence: 99%
“…In fact, some recent research has found that Asians may prefer to use a primary coping control as opposed to secondary coping (Sawaumi, Yamaguchi, Park, & Robinson, 2015). A recent study by English et al (2015), found that secondary coping was adaptive for both Westerners and (non-Chinese) Asians living in China. Further attention needs to be given to secondary coping regarding its benefits for situational stress and the impact of environment on coping styles.…”
Section: Discussionmentioning
confidence: 99%